المؤسسات الإسلامية ودورها فى إرساء السلام الاجتماعى - عبدالشكور، هانى بن أحمد Abdulalshakour, Hany ibn Ahmed (جامعة الملك عبدالعزيز, 2018)
يراد بالمؤسسات الإسلامية تلك التي تساهم في تنفيذ بعض البرامج الإسلامية في المجتمع من خلال المسجد والأوقاف والعمل الخيري والدعوي وهذا البحث محاولة في بيان إتيان الإسلام برسالة السلام الواضحة في مقاصده العليا ومن ثم دور هذه المؤسسات في تحقيق وإرساء السلام في المجتمع من خلال دورها الوظيفي، وتناول البحث ثلاثة نماذج منها وهي المسجد والأوقاف والقطاع الثالث، وكان من نتائج البحث أهمية دعم هذه المؤسسات وتنميتها وتسهيل مهامها ومراقبة ما يحتاج لمراقبة لما لذلك من أثر كبير في تحقيق السلم على المجتمع والأمة وتحقيق مقاصد الشريعة.
Islamic institutions are intended to contribute to the implementation of some Islamic programs in the community through the mosque and endowments and charitable work and advocacy. This research is an attempt to demonstrate the two pillars of Islam in the clear message of peace in its supreme objectives and then the role of these institutions in achieving and establishing peace in society through its functional role and dealing with three models, namely, mosque, endowments and the third sector. They need to be monitored because of their significant impact in achieving peace on society and the nation and to achieve the purposes of the law.
Keywords: المؤسسات الإسلامية -- السلم -- السلام الاجتماعى